Fluoride content in beverages of frequent intake by children at risk age of dental fluorosis. Medellín, 2006 - López, Diego Andrés; Franco, Ángela María; Estrada, Jeisson Javier; Zapata, Jonathan Andrés (Revista Facultad de Odontología Universidad de Antioquia, 2009)
Introduction: like others cities in the world, the prevalence of dental fluorosis has increased in Medellin, along with a reduction in dental caries. These changes have been attributed in part to the widespread use of systemic and topical fluorides. The purpose of this study was to analyze the fluoride content of beverages consumed by boys and girls of age susceptible to dental fluorosis. Methods: several kinds of beverages of 40 commercial brands (bottled waters, milk, natural juices, carbonated drinks, soft drinks and teas), purchased from supermarkets and grocery stores were analyzed. The fluoride content of all samples was determined in duplicate, using a Fluoride Ion Selective Electrode. Results: fluoride ion concentrations ranged from 0.010 to 4.285 mg/L. The majority of beverages presented fluoride levels below 0.058 mg/L. The highest mean concentration of fluoride was found in teas (3.45 ± 1.49 mg/L; range 1.54-4.28 mg/L). The manufacturers’ labelling did not inform about the content of fluoride concentration. Conclusions: the majority of beverages did not reach the fluoride level to be considered a risk for fluorosis; however, some of the analyzed beverages may be important contributors to the total daily F intake. Their consumption by children at the age of risk for dental fluorosis should be avoided. The F content in these products should be informed on their labels.